Increased Body Mass Index is Associated with Worse Mid- To Long-Term Patient Outcomes after Surgical Repair of Multiligamentous Knee Injuries - Tan, Danny; Ferrante, Stephanie; DiBartola, Alex; Magnussen, Robert; Welder, Eric; Crouser, Nisha; Kaeding, Christopher; Flanigan, David; Duerr, Robert A. (The Journal of Knee Surgery, 2023)
We evaluated the relationship between elevated body mass index (BMI) and mid- to long-term outcomes after surgical treatment of multiligamentous knee injury (MLKI). Records identified patients treated surgically for MLKI at a single institution. Inclusion criteria: minimum 2 years since surgery, complete demographics, surgical data, sustained injuries to two or more ligaments in one or both knees, and available for follow-up. Patients were contacted to complete patient-reported outcomes assessments and were classified according to mechanism of injury. Multivariate logistic regression analysis was used to predict the impact of BMI on outcome scores. A total of 77 patients (72.7% male) were included with a mean age at the time of injury of 29.4 ± 11.0 years and a mean BMI of 30.5 ± 9.4 kg/m2. The mean length of follow-up was 7.4 years. For each 10 kg/m2 increase in BMI, there is a 0.9-point decrease in Tegner activity scale (p = 0.001), a 5-point decrease in Knee Injury and Osteoarthritis Outcome Score (KOOS)-pain (p = 0.007), a 5-point decrease in KOOS-ADL (p = 0.003), a 10-point decrease in KOOS-QOL (p = 0.002), and an 11-point decrease in KOOS-Sport (p = 0.002). There were no significant correlations with BMI and Pain Catastrophizing Scale or Patient Health Questionnaire scores. Increasing BMI has a negative linear relationship with mid- to long-term clinical outcomes including pain, ability to perform activities of daily living, quality of life, and ability to perform more demanding physical activity after MLKI. BMI does not appear to have a significant relationship with knee swelling and mechanical symptoms or patients' mental health.
Keywords: body mass index; multiligamentous knee injury; clinical outcomes; anterior cruciate ligament; posterior cruciate ligament; medial collateral ligament; lateral collateral ligament